Information security management principles: an ISEB Certificate - Alexander, David; Taylor, Andy;Finch, Amanda;Sutton, David (Swindon, U.K. : British Computer Society, 2008)
How safe is your information? Recent events show that commercial, personal and sensitive information is very hard to keep secure, and some estimates point to 2007 as being the worst year on record for data loss. As breaches in information security continue to make headline news, it is becoming increasingly clear that technological solutions are not the only answer. Research conducted in 2007 suggests that at least 80% of data leakages are caused by staff rather than IT systems (source: Financial Times/Forrester Research, Nov-07). It is clear therefore that Information Security should be viewed as a management function rather than one of IT alone. Here, the authors outline the main management principles designed to help you secure your data, and raise awareness of the issues involved.
Copyright; Contents; List of Figures and Tables; Authors; Acknowledgements; Abbreviations; Preface; 1 Information Security Principles; 2 Information Risk; 3 Information Security Framework; 4 Information Security Controls; Index; Back Cover
Includes bibliographical references and index.
Keywords: COMPUTER SECURITY -- MANAGEMENT EXAMINATIONS -- STUDY, GUIDES